Disulfide HMGB1 derived from platelets coordinates venous thrombosis in mice - Stark, Konstantin; Nawroth, Peter Paul (Blood, 2016)
Key Points. Sterile inflammation inducing venous thrombosis is coordinated by the damage-associated molecular pattern HMGB1 delivered by platelets.
Gesehen am 13.05.2020